Uganda : Teachers - World Bank (Washington, DC, 2014)
There is increasing interest across the globe in attracting, retaining, developing, and motivating great teachers. Student achievement has been found to correlate with economic and social progress (Hanushek and Woessmann 2007, 2009; Pritchett and Viarengo 2009; Campante and Glaeser 2009), and teachers are key: recent studies have shown that teacher quality is the main school-based predictor of student achievement and that several consecutive years of outstanding teaching can offset the learning deficits of disadvantaged students (Hanushek & Rivkin 2010; Rivkin, et al. 2005; Nye et al. 2004; Rockoff 2004; Park and Hannum 2001; Sanders and Rivers 1996). However, achieving the right teacher policies to ensure that every classroom has a motivated, supported, and competent teacher remains a challenge, because evidence on the impacts of many teacher policies remains insufficient and scattered, the impact of many reforms depends on specific design features, and teacher policies can have very different impacts depending on the context and other education policies in place.